A Wide Scanning Array of Connected Bowtie Antennas Suitable for Integration in Composite Sandwich Structures With Monte-Carlo Tolerance Analysis - Prabhat Khanal (IEEE, 2021)
A low-profile and wide-scan phased-array antenna of connected cross-bowtie elements is proposed. The design goals and considerations are based on the applications requiring the integration of a large array antenna with composite sandwich structures, such as antennas on aircraft. In a very large array environment (modelled approximately as an infinite array), the main beam of the proposed antenna can be steered up to ±75° at azimuth and ±15° at elevation over bandwidths of 10% and 25% with active reflection coefficients below −10 dB and −5 dB, respectively. A Monte Carlo analysis of critical manufacturing and alignment tolerances shows the desired performance is achieved with the cumulative distribution probability over 80% under the uniformly distributed random combinations of the tolerances. Experimental results of a $7× 7$ element array prototype agree well with the simulations of this small-scale array case. The experiments show that this small-scale prototype is capable of steering the beam within the range of [−60°, 60°] at azimuth and [−15°, 15°] at elevation with the predicted performance satisfying the targeted application requirements and mechanical constraints. The achieved combination of the wide beam steering performance, relatively low antenna profile, and suitability of its feeding structure for sandwiched electro-mechanical integration makes this design unique with respect to the previously published results.